Interfacial reactions between carbon fiber and ceramic matrix in the short carbon fiber reinforced SiC-BN-10%X (X=ZrC, ZrO2 or ZrB2) composites - Pengfei Zhang; Guangchao Yang; Lingfeng Zhang; Renhong Yu; Jingling Ma; Bin Yang; Shizhong An; Bo Pang (Open Ceramics, 2022)
The short carbon fiber (Csf) reinforced SiC-BN-10%X (X = ZrC, ZrO2 or ZrB2) composites were prepared by hot pressing at 1900 °C and 40 MPa for 1 h. The phase composition and fracture morphology of the prepared composites were investigated, and the interfacial reactions between carbon fiber and ceramic matrix were discussed. The results show that ZrC, ZrB2 and ZrO2 all react with the Csf/SiC-BN system to form a lot of ZrB2 and ZrC, and the carbon fibers in all composites are corroded and damaged. The carbon atoms from ZrC and carbon fiber react with oxide film (ZrO2, B2O3, SiO2) or transition products (ZrSiO4, B4C) to form ZrC, ZrB2, SiC and CO. The interplanar spacing of the ZrC grains in the prepared composites decreases due to the consumption and shortage of carbon atoms. In the Csf/SiC-BN-10%ZrO2 composite, ZrO2 is completely reacted and almost all carbon fibers are exhausted.